1999
DOI: 10.1029/1999gl900508
|View full text |Cite
|
Sign up to set email alerts
|

Connections among ice, runoff and atmospheric forcing in the Beaufort Gyre

Abstract: and Ba profiles near the initial SHEBA site and, in 1997, we ran a section out to SHEBA. Resolving fresh water into runoff and ice reel't, we found a large background of Mackenzie River water with exceptional amounts in 1997 explaining much of the freshcuing at SHEBA. Ice melt went through a dramatic 4-6 m jump in the early 1990s coinciding with the atmospheric pressure field and sea-ice circulation becoming more cyclonic. The increase in sea-ice melt appears to be a thermal and mechanical response to a circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(141 citation statements)
references
References 23 publications
5
136
0
Order By: Relevance
“…According to our observations, the river plume extended far from the western channel of the river mouth to the northwest direction over 150 km. This result is consistent with that reported by Macdonald et al (1999). The slope of a CDOM (440) versus salinity in the present study was significantly different from that of Bélanger et al (2006) (p < 0.0001; Fig.…”
Section: Linkages Among Cdom Absorption Doc Concentrations and Hydrsupporting
confidence: 83%
“…According to our observations, the river plume extended far from the western channel of the river mouth to the northwest direction over 150 km. This result is consistent with that reported by Macdonald et al (1999). The slope of a CDOM (440) versus salinity in the present study was significantly different from that of Bélanger et al (2006) (p < 0.0001; Fig.…”
Section: Linkages Among Cdom Absorption Doc Concentrations and Hydrsupporting
confidence: 83%
“…For example, Guay and Falkner (1997) concluded, based on the dissolved barium concentration, that large amount of river discharge was present near the North American continental slope in 1993. Several studies (McPhee et al, 1998;Macdonald et al, 1999;Kadko and Swart, 2004) conducted at the SHEBA observation site in 1997 reported anomalously low salinities. The freshening in 1997 was traced to partly originate in the Mackenzie discharge, which likely contributes also to the elevated freshwater (Fig.…”
Section: The 1990smentioning
confidence: 99%
“…10), may have been generated either if dense waters were being formed inshore or if other sources of higher salinity waters existed inshore and were leaking out across the shelf [60][61][62]. We did not sample further inshore than the stations shown, so conditions further inshore are unknown.…”
Section: Vertical Sections and Salinitymentioning
confidence: 99%
“…It has been suggested that the northern Chukchi Sea, the Beaufort Sea, and the southern Canada Basin all have oligotrophic productivities because the surface waters lack high nutrient concentrations and the strong primary pycnocline prevents significant input of deep-water nutrients [27,62,63]. Our vertical sections (Fig.…”
Section: The Mesoscale Distribution Of Nitratementioning
confidence: 99%